Bima Bay Wiring, Natural Phenomenon Versus Pollution: a Review - Asryadin Asryadin; Syarifuddin Syarifuddin; Nahrio Nahrio; M. Sidik; Lalu Addien Faqih Panjenengan; Agus Ramdani; M. Yustiqvar (IKIP Mataram, 2022)
The incident that occurred some time ago in Bima Bay, West Nusa Tenggara Province, which began to be seen on April 25/26 2022 is a phenomenon that is quite horrendous for residents of the City/Regency of Bima and outside the Bima area. According to several preliminary studies based on laboratory tests and local inspections, it is estimated that there are three possible causes, namely: (1) Sea Snot, (2) Algae Explosion and Metabolism (Algae Blooms) and (3) Oil Spill (Algae Blooms). oil spill). This study aims to examine the assessment of the sea on human health and welfare, in particular to examine the causes of seawater phenomena that occur in Bima Bay by considering many aspects. This study identifies and makes estimates based on data and facts that relate the phenomena that occur/pollutants to health effects on marine biota and on humans. It was carried out by observing the quality of sea water in Bima Bay based on the results of several laboratory tests on specimens taken on 27-29 April 2022. The test results of sea water samples taken on 27 April 2022 showed a high nitrate content. levels of 9.75 mg/l to 34.75 mg/l (water quality standard for nitrate content = 0.008 mg/l) and accompanied by an increase in ammonia level of 0.41 mg/l (water quality standard for ammonia content = 0, 3 mg/l) l). l) and phosphate content of 0.06-0.08 mg/l (Phosphate quality standard = 0.015 mg/l). Total ammonia, nitrate and phosphate are environmental parameters that contain nutrients which if present in high concentrations and even continue to increase in marine waters will cause eutrophication (bloom) which can be very dangerous for other marine biota by causing a decrease in dissolved oxygen, plankton growth which can cause decrease in fish population, bad smell, and bad taste and can cause the formation of biomass in the form of jelly. The biomass can be in the form of polysaccharides and proteins with an estimated containing bacteria, viral pathogens known as sea snot.